2020
DOI: 10.1177/1044207320981781
|View full text |Cite
|
Sign up to set email alerts
|

Disability Type, Financial Capability, and Risky Asset Holding

Abstract: Risky financial asset holding is considered an indicator of financial well-being because risky asset holders are likely to accumulate more wealth than nonholders. Like the general population in the United States, many people with disabilities need long-term financial planning services. The purpose of this study was to examine whether disability type and financial capability are associated with risky asset holding of adults with disabilities. Using data from the 2015 National Financial Capability Study, we foun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 31 publications
0
5
0
Order By: Relevance
“…The development and implementation of the Financial Capability Framework typically entail collaboration across multiple sectors, including government, education, financial services, and community organizations. This cross-sector cooperation enables sharing resources, expertise, and best practices, facilitating more effective and sustainable interventions to enhance financial capability and well-being (Xiao & O'Neill, 2022;Bangma et al, 2021;Hill & Sharma, 2020). In essence, the Financial Capability Framework offers a comprehensive approach to promoting financial literacy, financial behavior, and financial wellbeing by addressing a diverse array of factors influencing individuals' capacity to manage their finances effectively.…”
Section: Financial Capability Frameworkmentioning
confidence: 99%
“…The development and implementation of the Financial Capability Framework typically entail collaboration across multiple sectors, including government, education, financial services, and community organizations. This cross-sector cooperation enables sharing resources, expertise, and best practices, facilitating more effective and sustainable interventions to enhance financial capability and well-being (Xiao & O'Neill, 2022;Bangma et al, 2021;Hill & Sharma, 2020). In essence, the Financial Capability Framework offers a comprehensive approach to promoting financial literacy, financial behavior, and financial wellbeing by addressing a diverse array of factors influencing individuals' capacity to manage their finances effectively.…”
Section: Financial Capability Frameworkmentioning
confidence: 99%
“…A few prior studies indicate that households with disabilities are financially fragile. Adults with work disabilities are less likely than adults with mental disabilities to hold risky financial assets which can result in lower financial well-being due to the inability to build household wealth (Xiao and O'Neill, 2022). People with psychiatric disorders were found to be financially incapable and mismanaged their money (Lazar et al, 2015(Lazar et al, , 2016.…”
Section: Literature Backdrop and Hypothesesmentioning
confidence: 99%
“…Observations were excluded from the study if data was "not identified," "not in universe" or "unknown" for any of the variables measuring banking status, AFS use, discouraged borrower status, monthly income volatility, savings account status or Internet access status. We also removed observations that had "yes" answers to every disability type similar to Xiao and O'Neill (2022). This resulted in 2,310 observations being dropped and the final sample size was 96,522 for measuring banking status and unmet demand for credit.…”
Section: Data and Sample Selectionmentioning
confidence: 99%
“…Building on previous research on financial capability, the three groups of psychological, demographic, and economic variables were included as control variables (see, e.g., Atkinson et al, 2007;Białowolski et al, 2019Białowolski et al, , 2021Kempson et al, 2005;Reyers, 2019;Salignac et al, 2019;Taylor, 2011;Taylor et al, 2011;Xiao et al, 2014;Xiao & O'Neill, 2020). The demographic variables consisted of eight variables, including: "age", "whether being unemployed", "education (years of education)", "number of persons in the household", "whether living alone in the home", "main employment and work status", "marital status" and "whether smoking".…”
Section: Independent Variablesmentioning
confidence: 99%
“…The following variables were selected as psychological variables: whether feeling income stability, whether not have felt hopelessness and not had experienced suicidal thoughts in the recent months, whether financial problems and worries not added to your troubles and not made your life more difficult than usual in the recent months, whether experiencing physical health problems obstructing from going out of the house in the recent months, active response to financial emergencies. Previous research showed that psychological and physical variables are highly relevant given that they may predict personal debt (Bridges & Disney, 2010), financial distress, and fragility (Białowolski et al, 2021;Kealy et al, 2018;Xiao & Kim, 2021), holding risky assets (Xiao & O'Neill, 2020) or more broadly financial capability (Taylor et al, 2011;Xiao et al, 2014).…”
Section: Independent Variablesmentioning
confidence: 99%